PRESERVATION OF CULTURAL HERITAGE IN THE CONTEXT OF GLOBALIZATION: SOCIAL ASPECTS AND PERSPECTIVES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Subject of the study – cultural heritage as a social phenomenon. Topic – preservation of cultural heritage in the context of globalization. Purpose – to analyze the social aspects of cultural heritage study and peservation, and to define its role in sustainable development of society. The article explores both theoretical and practical approaches to safeguarding cultural values such as traditions, rituals, oral folklore, and architectural monuments. Special attention is given to the role of youth, governmental and educational institutions, and digital technologies in transmitting cultural knowledge. The study includes examples from Kyrgyz and international contexts, including France, Japan, and UNESCO initiatives. Results indicate that cultural heritage preservation strengthens social identity, intergenerational cohesion, patriotism, and social resilience. Application areas – cultural policy, education, social work, cultural tourism, digital technologies. Conclusion – cultural heritage is a vital resource for social development and its preservation requires an interdisciplinary and participatory approach.
Keywords: Сultural heritage; social identity; traditions; patriotism; intergenerational continuity; social cohesion; cultural values; folklore; cultural memory; globalization